THE DEPICTION OF THE KARAKHANID DYNASTY'S HISTORY IN TURKISH HISTORIOGRAPHY (Western European Journal of Historical Events and Social Science, 2025)
This article analyzes the coverage in Turkish historiography of issues related to the origins of the Karakhanid dynasty, the state structure of their empire, the friendly and hostile relations between the Karakhanids and Ghaznavids, the dynasty's acceptance of Islam, and changes in architecture and culture.